Biological and chemical properties of five mineral oxides and of mineral trioxide aggregate repair high plasticity: an in vitro study - Abu Hasna, Amjad [UNESP]; de Paula Ramos, Lucas [UNESP]; Campos, Tiago Moreira Bastos; de Castro Lopes, Sergio Lucio Pereira [UNESP]; Rachi, Maisour Ala; de Oliveira, Luciane Dias [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (Springer Nature, 2022)
Calcium silicate-based cements have diverse applications in endodontics. This study aimed to evaluate the antibiofilm action, biocompatibility, morphological structure, chemical composition and radiopacity of Five Mineral Oxides (5MO), Mineral Trioxide Aggregate Repair High Plasticity (MTA Repair HP), and Mineral Trioxide Aggregate (MTA) cements. MTT analysis was used to test the antibiofilm action of these cements against five anaerobic microorganisms, and test their biocompatibility with mouse macrophage (RAW 264.7) and osteoblasts (MG-63) cultures. Their morphological structure and chemical composition were evaluated by scanning electron microscopy (SEM) coupled to energy dispersion X-ray spectroscopy (EDX), and the phase analysis was performed by X-ray diffraction (XRD). Conventional radiography was used to assess the radiopacity of the cements. 5MO, MTA Repair HP and MTA were effective against Porphyromonas gingivalis, Parvimonas micra, Fusobacterium nucleatum and Prevotella intermedia, they were biocompatible with macrophages and osteoblasts after 5 min of contact, and they had adequate radiopacity to be used clinically. Bismuth oxide (Bi2O3) is used as a radiopacifier in MTA and 5MO, and calcium tungstate, in MTA Repair HP. Titanium dioxide (TiO2) (ANATASE) is responsible for the antimicrobial action and biocompatibility of 5MO.